Mechanisms, screening modalities and treatment options for individuals with non‐alcoholic fatty liver disease and type 2 diabetes. Issue 11 (13th July 2020) - Hydes, T. J.; Summers, N.; Brown, E.; Alam, U.; Thomaides‐Brears, H.; Wilding, J. P. H.; Cuthbertson, D. J.
Abstract: Non‐alcoholic fatty liver disease (NAFLD) exists as a spectrum of disease ranging from excessive accumulation of fat within the liver (simple steatosis), inflammation (non‐alcoholic steatohepatitis) through to fibrosis, cirrhosis and end‐stage liver disease. There is also an increased risk of hepatocellular carcinoma. The principal risk factor for NAFLD is overweight or obesity, along with type 2 diabetes, and NAFLD itself is also a risk factor for incident type 2 diabetes. Overweight/obesity is synergistic with alcohol consumption in causing progressive and insidious liver damage. Recent consensus advocates a change in nomenclature from NAFLD to 'metabolic associated fatty liver disease' (MAFLD), reflective of the associated metabolic abnormalities (insulin resistance/type 2 diabetes and metabolic syndrome components). Additional extra‐hepatic manifestations of NAFLD include cardiovascular disease, chronic kidney disease and certain cancers. Unlike other micro‐ and macrovascular complications of type 2 diabetes, systematic screening or surveillance protocols have not been widely adopted in routine diabetes care to assess for presence/severity of NAFLD. Various screening tools are available (non‐invasive tests and biochemical indices) combined with imaging techniques (e.g. transient elastography) to detect steatosis and more importantly advanced fibrosis/cirrhosis to facilitate appropriate surveillance. Liver biopsy may be sometimes necessary. Treatment options for type 2 diabetes, including lifestyle interventions (dietary change and physical activity), glucose‐lowering therapies and metabolic surgery, can modulate hepatic steatosis and to a lesser extent fibrosis. Awareness of the impact of liver disease on the choice of glucose‐lowering medications in individuals with type 2 diabetes is also critical. What's new?: Individuals with type 2 diabetes have a near threefold higher risk of dying from chronic liver disease. The presence of non‐alcoholic fatty liver disease (NAFLD) has implications for liver disease progression, microvascular and macrovascular complications of diabetes, and additional extra‐hepatic manifestations. Screening for NAFLD, followed by risk stratification to identify individuals with liver fibrosis, should be adopted into routine diabetes care. Significant weight loss of 7–10% can cause regression of histological abnormalities including of fibrosis, in non‐alcoholic steatohepatitis, even at advanced stages. Thiazolidinediones, glucagon‐like peptide‐1 (GLP1) receptor agonists and sodium–glucose co‐transporter 2 (SGLT2) inhibitors have all been shown to improve hepatic steatosis. The only currently available data on histological improvement relate to the use of thiazolidinediones and GLP1 receptor agonists but is lacking in the case of SGLT2 inhibitors.